Strategy for Procurement of Imported Sesame Seed Raw Materials at PD Linggar Sari - Syahid Jayyidan, Aqil; Indika, Deru R (Jurnal Multidisiplin Indonesia, 2024)
The resources of each country are different. These results in countries trading internationally. Sesame is a commodity that has potential in the culinary industry. Sesame is categorized as quality if the cultivation of the plant is carried out on dry land or places with low rainfall. Most fellow producers in Indonesia have poor quality standards, and some even fail to harvest due to the unfavorable climate for producing sesame commodities. PD Linggar Sari is a small and medium enterprise (UKM) that produces sesame-married cakes and one-time seeds as complementary raw materials. Initially, PD Linggar Sari used 500 kg of imported Indian sesame seeds weekly, which were obtained through local importers. However, due to supply uncertainty, Pd Linggar Sari switched to local sesame seeds. However, this transition has an impact, namely a decrease in income of approximately 15% to 20% per year due to a decrease in product quality. This research aims to provide information to PD Linggar Sari regarding analyzing imported sesame seed procurement strategies. The method used is the Analysis Hierarchy Process with the types of data used, namely secondary and primary data. There are three alternatives for procuring imported sesame seeds: local importers, global marketplaces, and direct imports. The results of the analysis of procuring imported sesame seeds show that direct importation is an alternative strategy for procuring imported seeds at PD Linggar Sari.